Single-phase and two-phase flow properties of mesaverde tight sandstone formation; random-network modeling approach. (August 2016) - Bashtani, Farzad; Maini, Brij; Kantzas, Apostolos
Highlights: 43 random networks are constructed in order to represent the selected samples. Macroscopic properties of the networks match the laboratory data. A power relationship was observed between Pbt and absolute permeability. The modified network model is capable of dealing with finite Pc at Swr . Primary drainage properties are predicted and successfully match MICP data. Results are consistent with physical expectations of quasi-static displacement. Abstract: 3D random networks are constructed in order to represent the tight Mesaverde formation which is located in north Wyoming, USA. The porous-space is represented by pore bodies of different shapes and sizes which are connected to each other by pore throats of varying length and diameter. Pore bodies are randomly distributed in space and their connectivity varies based on the connectivity number distribution which is used in order to generate the network. Network representations are then validated using publicly available mercury porosimetry experiments. The network modeling software solves the fundamental equations of two-phase immiscible flow incorporating wettability and contact angle variability. Quasi-static displacement is assumed. Single phase macroscopic properties (porosity, permeability) are calculated and whenever possible are compared to experimental data. Using this information drainage and imbibition capillary pressure, and relative permeability curves are predicted and (whenever possible) compared to experimental data. The calculated information is grouped and compared to available literature information on typical behavior of tight formations. Capillary pressure curve for primary drainage process is predicted and compared to experimental mercury porosimetry in order to validate the virtual porous media by history matching. Relative permeability curves are also calculated and presented.